An interlaboratory comparison of nanosilver characterisation and hazard identification: Harmonising techniques for high quality data. (February 2016) - Jemec, Anita; Kahru, Anne; Potthoff, Annegret; Drobne, Damjana; Heinlaan, Margit; Böhme, Steffi; Geppert, Mark; Novak, Sara; Schirmer, Kristin; Rekulapally, Rohit; Singh, Shashi; Aruoja, Villem; et al.
Abstract: Within the FP7 EU project NanoValid a consortium of six partners jointly investigated the hazard of silver nanoparticles (AgNPs) paying special attention to methodical aspects that are important for providing high-quality ecotoxicity data. Laboratories were supplied with the same original stock dispersion of AgNPs. All partners applied a harmonised procedure for storage and preparation of toxicity test suspensions. Altogether ten different toxicity assays with a range of environmentally relevant test species from different trophic levels were conducted in parallel to AgNP characterisation in the respective test media. The paper presents a comprehensive dataset of toxicity values and AgNP characteristics like hydrodynamic sizes of AgNP agglomerates and the share (%) of Ag + -species (the concentration of Ag + -species in relation to the total measured concentration of Ag). The studied AgNP preparation (20.4 ± 6.8 nm primary size, mean total Ag concentration 41.14 mg/L, 46–68% of soluble Ag + -species in stock, 123.8 ± 12.2 nm mean z-average value in dH2 O) showed extreme toxicity to crustaceans Daphnia magna, algae Pseudokirchneriella subcapitata and zebrafish Danio rerio embryos (EC50 < 0.01 mg total Ag/L), was very toxic in the in vitro assay with rainbow trout Oncorhynchus mykiss gut cells (EC50: 0.01–1 mg total Ag/L); toxic to bacteria Vibrio fischeri, protozoa Tetrahymena thermophila (EC50: 1–10 mg total Ag/L) and harmful to marine crustaceans Artemia franciscana (EC50: 10–100 mg total Ag/L). Along with AgNPs, also the toxicity of AgNO3 was analyzed. The toxicity data revealed the same hazard ranking for AgNPs and AgNO3 (i.e. the EC50 values were in the same order of magnitude) proving the importance of soluble Ag + -species analysis for predicting the hazard of AgNPs. The study clearly points to the need for harmonised procedures for the characterisation of NMs. Harmonised procedures should consider: (i) measuring the AgNP properties like hydrodynamic size and metal ions species in each toxicity test medium at a range of concentrations, and (ii) including soluble metal salt control both in toxicity testing as well as in Ag + -species measurements. The present study is among the first nanomaterial interlaboratory comparison studies with the aim to improve the hazard identification testing protocols. Graphical abstract: Highlights: Harmonisation of protocols leads to high quality hazard identification data. Soluble metal salt control should be an integral part of nanomaterial testing. Aging of nanomaterials should be considered in test procedures. The same hazard ranking for AgNPs and AgNO3 AgNPs EC50: D. magna, algae, D. rerio ˂ V. fischeri ˂ T. thermophila ˂ A. salina